Evaluasi Kinerja Metode Perhitungan Koefisien Pengaliran: Evaluation of Runoff Coefficient’s Calculation Methods Performance - Humairo Saidah; Lalu Wirahman; Lia Hidayaturrohmi (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
The runoff coefficient dramatically affects the volume of surface runoff. The better the method for determining the runoff coefficient, the more precise the estimation of the amount of surface runoff will be so that it can support planning for the management of water resources in an area more effectively. Several runoff coefficient calculation techniques, such as the U.S. Forest Service method, Hassing and Cook use different approaches to produce runoff coefficients. This study examines the accuracy of those methods in producing runoff coefficients by comparing the coefficients obtained from the methods with the actual flow coefficients obtained from measurement data. The results showed that the closest runoff coefficient to the coefficient of measurement one is by the U.S. Forest Service method using the median of the value intervals provided in the USFS table. The second and third best methods are the Hassing and U.S. Forest Service for maximum value.